Integrating 7KAIH into IPAS Learning for Students’ Social Character Development in Elementary School - Yeni Siti Rokayah; Lili Halimah; Arnie Fajar (Educenter : Jurnal Ilmiah Pendidikan, 2026)
This study examines the integration of the 7 Kebiasaan Anak Indonesia Hebat (7KAIH) program into Ilmu Pengetahuan Alam dan Sosial (IPAS) learning and its contribution to the development of students’ social character at SDN Walahir, West Bandung Regency. This research employs a qualitative descriptive approach involving one school principal, two IPAS teachers, and twelve students selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings reveal that the integration of 7KAIH into daily school routines and IPAS learning activities effectively fosters students’ social character, particularly in terms of empathy, cooperation, and responsibility. The program is implemented through habitual activities such as morning greetings, collaborative learning, reflective discussions, and contextual IPAS projects. However, challenges were identified, including inconsistent implementation among teachers and limited parental involvement. The novelty of this study lies in its focus on the integration of a national character education program (7KAIH) into subject-based learning (IPAS), providing a practical model for embedding character education within classroom instruction. The study implies that strengthening collaboration between schools and families, as well as enhancing teacher consistency, is essential to optimize the effectiveness of character education programs in elementary schools.